Beneath the Surface: Hidden Emotional Conflicts in ʿĀʾid ilā Ḥayfā from a Freudian Perspectivev - Anggi Yulia Sari; Mohamad Rohman; Yetti Hasnah (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2026)
This study addresses the problem of how hidden emotional patterns operate within literary characters shaped by collective trauma, particularly in Ghassan Kanafani’s ʿĀʾid ilā Ḥayfā. It aims to analyze the forms and dynamics of these latent emotions in the characters of Said and Safiyya through Sigmund Freud’s psychoanalytic framework. The research employs a descriptive qualitative method, using intensive reading and systematic note-taking to interpret narrative elements and psychological expressions within the text. The findings reveal that trauma is manifested through the structural interaction of the Id, Ego, and Superego. Said demonstrates a dominant Ego pattern, rationalizing instinctive impulses and moral pressures into ideological reasoning. In contrast, Safiyya reflects an Ego collapse marked by panic, which is ultimately stabilized by the Superego through maternal responsibility. These dynamics illustrate the internal struggle between personal desire, moral obligation, and historical burden. The study contributes to literary criticism by offering a psychoanalytic interpretation of post-Nakba identity formation and highlighting how individual psychological conflict mirrors broader collective fragmentation in Palestinian society.